Konversi Minyak Sawit Menjadi Biodiesel dengan Katalis Abu Sekam Padi - Arman, Fikry Naufal; Primandari, Sri Rizki Putri (Darul Yasin Al Sys, 2023)
Based on data from the Coordinating Ministry for the Economy, in 2022 Indonesia will contribute 52% of palm oil to the world market share and will be able to produce 40% of the world's total vegetable oil, this will encourage Indonesia to increase the use of biofuels such as biodiesel.Rice husks are still not well utilized so they only become piles of waste. This research aims to determine the effect of rice husk ash as a catalyst in making biodiesel. Rice husks contain compounds as catalyst support, namely SiO2.At this tranesterification stage, two types of treatment are given, namely variations in temperature and catalyst concentration to see the best comparison of the several types of samples. The transesterification stage uses a 1:1 ratio of oil and methanol and the addition of 1% KOH. The results of this stage produce biodiesel with characteristics, namely a density ranging from 857.2-862.4 Kg/m3 and a viscosity in the range 3.25-4.48 mm2/s which meets SNI biodiesel standards. From this research it can be concluded that rice husk ash has the potential as a heterogeneous catalyst in making biodiesel to replace homogeneous catalysts.